If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(x + 7) = 5x + -35 Reorder the terms: -9(7 + x) = 5x + -35 (7 * -9 + x * -9) = 5x + -35 (-63 + -9x) = 5x + -35 Reorder the terms: -63 + -9x = -35 + 5x Solving -63 + -9x = -35 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -63 + -9x + -5x = -35 + 5x + -5x Combine like terms: -9x + -5x = -14x -63 + -14x = -35 + 5x + -5x Combine like terms: 5x + -5x = 0 -63 + -14x = -35 + 0 -63 + -14x = -35 Add '63' to each side of the equation. -63 + 63 + -14x = -35 + 63 Combine like terms: -63 + 63 = 0 0 + -14x = -35 + 63 -14x = -35 + 63 Combine like terms: -35 + 63 = 28 -14x = 28 Divide each side by '-14'. x = -2 Simplifying x = -2
| 9y-33=3(y+7) | | 4(x+7)=-4x+4 | | 3x+(-7)=-25 | | 8y-32=-8(y+6) | | 25x^2-45x+8= | | 5x^2-36x+36= | | 35-19=2(x-8) | | graphy=-2x-4 | | 3x^2/5=27 | | 4k^2-9= | | 1.2y=3+y+1 | | 3y=8+y+1 | | 10x^2-41x-45= | | -9x=6 | | 2v+7-5v=-17 | | 7=-3+9 | | 3y=y+3+1 | | .03(x+40)+12.8=.4(10-x)+96 | | (3x-5)(-5)= | | 27x^2-246x-240= | | 6(5-x)-3(x-4)=6 | | p^2+p-20=0 | | 46-11=5(x-8) | | 6x^2-x+3=0 | | 4x^2-10x+25=49 | | 64-6x=12x+16 | | 10x^2-80x= | | 12-8x=111-29 | | 8w^3-3w+1=0 | | 4(2-3x)-30=10-2(x-4) | | 27x-30x=7-10 | | 9/x=15/35 |